2020
DOI: 10.1186/s13014-020-01692-3
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram based on pretreatment CT radiomics features for predicting complete response to chemoradiotherapy in patients with esophageal squamous cell cancer

Abstract: Purpose To develop and validate a nomogram model to predict complete response (CR) after concurrent chemoradiotherapy (CCRT) in esophageal squamous cell carcinoma (ESCC) patients using pretreatment CT radiomic features. Methods Data of patients diagnosed as ESCC and treated with CCRT in Shantou Central Hospital during the period from January 2013 to December 2015 were retrospectively collected. Eligible patients were included in this study and randomize divided into a training set and a validation set after … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…Furthermore, Liu et al. developed and validated a nomogram based on pretreatment CT radiomics features for predicting complete response to chemoradiotherapy ( 22 ). CT-based radiomics has also been applied to tumor stage assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Liu et al. developed and validated a nomogram based on pretreatment CT radiomics features for predicting complete response to chemoradiotherapy ( 22 ). CT-based radiomics has also been applied to tumor stage assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging studies suggest that robust prediction of patient response to CCRT could also be achieved by using a variety of other methodologies, including molecular signature, CT-radiomics, and positron emission tomography. [41][42][43] Combining these markers with PBCS may lead to a greater predictive capability for patient outcomes.…”
Section: Dovepressmentioning
confidence: 99%
“…Aerts et al (20) found that the radiomics model was able to capture intratumoral heterogeneity and was significantly associated with the gene-expression profile pattern. Moreover, results from various studies showed high correlation between radiomic features and prognostic outcomes, such as in head and neck cancer (21,22), esophageal cancer (23,24), and nasopharyngeal cancer (25,26).…”
Section: Introductionmentioning
confidence: 99%